Geopolitical Implications of the Russia-China Nexus: Power Dynamics and Regional Impact on South Asia (2003-2023) - Roy, Nadeem Abbas; Shahzad, Sajid Mehmood (Annals of Human and Social Sciences, 2025)
This paper gives a detailed analysis of South Asia’s shifting geopolitical landscape, focusing on the strategic interaction between Russia-China’s developing alliance and the United States. China and India emerged as economic superpowers in the new world. China and Russia’s deepening strategic coordination has far-reaching ramifications. Pakistan’s strategic location is critical to the broader geopolitical conflict. The regional power dynamics are rapidly changing. Hence, this alliance may disrupt the Indo-US partnership. It considers both regional power dynamics and global rivalry, which have consequences for the future of South Asian geopolitics. A mixed-methods research approach was adopted. Content analysis demonstrates South Asian attitudes toward economic and strategic gains. These impressions shape regional foreign policy decisions. Case studies and statistical analyses highlight important trends and patterns. These patterns demonstrate robust relationships throughout the study period, from Realism to Economic Statecracft and Regional Security Complex Theories. Hence, this study provides important insights on South Asian geopolitics.